State‐of‐the‐Art Design and Rapid‐Mixing Production Techniques of Lipid Nanoparticles for Nucleic Acid Delivery. Issue 9 (26th April 2018) - Evers, Martijn J. W.; Kulkarni, Jayesh A.; van der Meel, Roy; Cullis, Pieter R.; Vader, Pieter; Schiffelers, Raymond M.
Abstract: Lipid nanoparticles (LNPs) are currently the most clinically advanced nonviral carriers for the delivery of small interfering RNA (siRNA). Free siRNA molecules suffer from unfavorable physicochemical characteristics and rapid clearance mechanisms, hampering the ability to reach the cytoplasm of target cells when administered intravenously. As a result, the therapeutic use of siRNA is crucially dependent on delivery strategies. LNPs can encapsulate siRNA to protect it from degradative endonucleases in the circulation, prevent kidney clearance, and provide a vehicle to deliver siRNA in the cell and induce its subsequent release into the cytoplasm. Here, the structure and composition of LNP–siRNA are described including how these affect their pharmacokinetic parameters and gene‐silencing activity. In addition, the evolution of LNP–siRNA production methods is discussed, as the development of rapid‐mixing platforms for the reproducible and scalable manufacturing has facilitated entry of LNP–siRNA into the clinic over the last decade. Finally, the potential of LNPs in delivering other nucleic acids, such as messenger RNA and CRISPR/Cas9 components, is highlighted alongside how a design‐of‐experiment approach may be used to improve the efficacy of LNP formulations. Abstract : Lipid nanoparticles (LNPs) are currently the most clinically advanced nonviral carriers for the delivery of small interfering RNAs (siRNAs). The current knowledge regarding LNP–siRNA design and the evolution of LNP–siRNA production methods focusing on microfluidic‐mixing techniques is reviewed. Additionally, the potential of LNPs for delivering other nucleic acids, such as messenger RNA and CRISPR/Cas9 components, is discussed.